The Efficacy of Hybrid Learning Process in SMA Islam Ibnu Umar Students Tangerang Selatan - Kurniawan Arif Maspul; Fina Amalia (CV. Ulil Albab Corp, 2022)
In uncertain conditions, the current pandemic has forced all schools to adopt the new pedagogy approach. It makes every student and teacher adapt to a renewable education system through hybrid learning. Therefore, it is aligned with teaching and learning activities and the essential competencies required for each school to implement and make this program a success. Moreover, through the hybrid system, it is necessary to experiment with a system of teaching and learning activities in Arabic language science, Islamic Studies, and memorising Tahfidz al-Quran, which has been taking place in the past semesters at SMA Islam Ibnu Umar Tangerang Selatan. The existence of good cooperation between students' teachers and other stakeholders from the family will help the success of this program, and it is expected that it will be sustainable in the long term.